The Verification of Thermoelectric Performance Obtained by High-Throughput Calculations: The Case of GeS2 Monolayer From First-Principles Calculations - Wang, Xiaolian; Feng, Wei; Shen, Chen; Sun, Zhehao; Qi, Hangbo; Yang, Mao; Liu, Yonghui; Wu, Yuchen; Wu, Xiaoqiang (Frontiers in Materials, 2021)
Electronic fitness function (EFF, achieved by the electrical transport properties) as a new quantity to estimate thermoelectric (TE) performance of semiconductor crystals is usually used for screening novel TE materials. In recent years, because of the high EFF values, an increasing number of two-dimensional materials have been predicted to have the potential for TE applications via high-throughput calculations. Among them, the GeS2 monolayer has many interesting physical properties and is being used for industrial applications. Hence, in this work, we systematically investigated the TE performance, including both electronic and thermal transport properties, of the GeS2 monolayer with first-principles calculations. The results show that the structure of the GeS2 monolayer at 700 K is thermally unstable, so we study its TE performance only at 300 and 500 K. As compared with other typical TE monolayers, the GeS2 monolayer exhibits excellent electronic transport properties but a relatively high lattice thermal conductivity of 5.71 W m−1 K−1 at 500 K, and thus an unsatisfactory ZT value of 0.23. Such a low ZT value indicates that it is necessary to consider not only the electron transport properties but also the thermal transport properties to screen the thermoelectric materials with excellent performance through high-throughput calculations.